[OP.7B.01] MASKED HYPERTENSIVES EXHIBIT AN EXAGGERATED BLOOD PRESSURE RESPONSE DURING HANDGRIP EXERCISE SIMILAR TO THAT IN HYPERTENSIVE INDIVIDUALS. (September 2017) - Koletsos, N.; Dipla, K.; Triantafyllou, A.; Sachpekidis, V.; Grigoriadou, I.; Zafeiridis, A.S.; Gkaliagkousi, E.; Anyfanti, P.; Zafeiridis, A.; Douma, S.
Abstract : Objective: Masked hypertension has been associated with increased risk for target organ damage and cardiovascular disease. Recent evidence indicate that hypertensive individuals exhibit exaggerated blood pressure (BP) response during exercise and delayed recovery, linked to excessive sympathetic stimulation and an overactive exercise pressor reflex. Whether individuals with masked hypertension (masked-HYP) also exhibit exaggerated BP and systemic vascular resistance (SVR) responses as true hypertensives (true-HYP) during exercise has not been investigated. Therefore, the aim of this study was to evaluate the cardiovascular responses during handgrip exercise and recovery in masked-HYP, true-HYP, and normotensive (NORMO) individuals. Design and method: Eighty six individuals participated in the present study: healthy-NORMO (n = 28), masked-HYP (n = 27), and true-HYP (n = 31). All hypertensive participants were newly diagnosed, untreated, with no other known cardiovascular disease. Following a complete history, physical examination, and blood testing, office and ambulatory BP were measured in order to determine their hypertensive status. All participants underwent an exercise protocol, consisting of a 3-min rest (baseline), a 3-min handgrip exercise at 30% maximal voluntary contraction (MVC), and a 3-min recovery. Beat-by-beat BP and heart rate (HR) were continuously assessed via photoplethysmography (Finapress) throughout the protocol and SVR was calculated. Results: There were no differences among the three groups in age, smoking status, body mass index, fasting blood glucose, lipid profile, and MVC. Masked-HYP exhibited similar baseline BP to NORMO, however, during HG-exercise, masked-HYP exhibited a markedly greater (p < 0.05) systolic/diastolic BP response compared with NORMO (174.8 ± 13.5/98.5 ± 7.0 vs. 159.2 ± 15.7/91.3 ± 9.2 mmHg, respectively) and similar BP responses to true-HYP (181.4 ± 14.5/101.8 ± 9.5 mmHg). In addition, during exercise, masked-HYP exhibited a significant increase in SVR (p < 0.05), similar to that observed in true-HYP, whereas no significant increase in SVR was observed in NORMO. During the 3-min post-exercise period, BP in masked-HYP declined and returned to values comparable to those in NORMO (p = 0.32). Conclusions: This is the first study to show that during isometric exercise, masked-HYP exhibit exaggerated BP and SVR responses, suggesting an overactive exercise pressor reflex in masked hypertension. The cardiovascular responses during exercise in masked-HYP are similar to those in true-HYP.